Perceived Value in Vocational Education: The Roles of Institutional Reputation, Curriculum Relevance, and Employability Outcomes - Sawatmuang, Pathom; Bordin Phayaphrom (Journal of Technical Education and Training, 2026)
The study examined the outcomes of vocational institution reputation, education quality, and employability on the perceived value of vocational education and the mediating effect of an industry-relevant curriculum through the Resource-Based View (RBV), Brand Equity Theory, Theory of Planned Behavior (TPB), and the Stakeholder Theory. The explanatory sequential mixed-method design was adopted. The quantitative analysis of survey data was based on 300 respondents: 150 employers and 150 learners in the vocational institution in Thailand. The in-depth interview included 10 employers and 10 learners using a qualitative thematic analysis. The statistical data through the Partial Least Squares Structural Equation Modeling (PLS-SEM) showed that internal quality and external market strengths are strong predictors of the perceived value, with the strength of the correlation on the relevance of the curriculum mediating. Turning to an industrial-focused curriculum was a better utilization of institutional strength, as suggested by the substantial mediation results. The multi-group analysis result showed no significant difference between employers and learners; hence, it suggests a high conversion rate in the perceptions of the stakeholders. The qualitative data analysis supported these findings and indicated that three key value drivers contributed to the perception: alignment of curriculum with industry needs, presence of evidence of employability outcomes, and consistent performance of the institution.